Strong Stabilization of Inhomogeneous Semilinear Systems - Alami, A. El; Chqondi, M. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we study feedback stabilization of inhomogeneous semi-linear control system on a Hilbert state space. The paper gives a feedback control that ensure the strong in term of approximate observability like assumptions. Applications to heat equations are provided.